ANALISIS DAN IMPLEMENTASI TEKNOLOGI ADAPTIVE BITRATE STREAMING TERHADAP KONDISI BANDWIDTH (Studi Kasus : Valu TV (PT Distribusi Media Teknologi)) - Iriyanti, Iindra; Arini, Arini; Arnaldy, Defiana (PETIR, 2015)
The growth of the internet and smart device users in Indonesia is quite rapidly and is expected to continue to increase each year . Internet users in Indonesia come from various backgrounds and ages . It is often done internet users are watching streaming video via their smart devices . More and more users are accessing internet streaming video it will affect the condition of the bandwidth provided by the ISP ( Internet Service Provider ) which would affect the user experience due to buffer the video stream when the video is being watched . Looking at these problems , a company engaged in the field of streaming TV ( PT Distribution Media Technology ) setting up a streaming TV service using a technology that is relatively new in Indonesia , namely Adaptive Bitrate Streaming technology that can solve the problems of the video stream buffer . Knowing that the Adaptive Bitrate Streaming technology is relatively new in Indonesia , the researchers tried to analyze the Adaptive Bitrate Streaming technology as well as the influence of bandwidth conditions for these technologies . In this study , researchers used a quantitative method to analyze the Adaptive Bitrate Streaming technology , implement the technology on several devices and analyze the effect of bandwidth on facility conditions VOD ( Video on Demand ) which is implemented using Adaptive Bitrate Streaming technology that existed at Valu TV service ( PT Distribution Media Technology ) . The results of this analysis is to find out how to work the Adaptive Bitrate Streaming technology and its implementation on bandwidth conditions while riding , stable , and down . With the Adaptive Bitrate Streaming technology , users can watch a video streaming video comfortably without buffer despite their internet bandwidth conditions are unstable.